Narasi kultur ekologi masyarakat desa kon novel haniyah dan ala di rumah teteruga karya Erni Aladjai - Latifah, Suci Ayu; Setiawan, Agus; Wahyuni, Sri (Aksara: Jurnal Bahasa dan Sastra, 2024)
The research on the narrative of the ecological culture of the Kon Village community is closely related to the novel Haniyah and Ala at Rumah Teteruga by Erni Aladjai. This study aims to describe the ecological culture in the novel set in Eastern Indonesia. The social activities of the characters are close to the natural, social, and cultural environments. The majority of the community's livelihoods are as farmers and clove laborers. In addition, as clove climbers, vegetable pickers, fishermen, teachers, and others. The analysis in the study uses the theory of literary ecoanthropology, which is a combination of two theories of literary ecology and literary anthropology. The research method uses qualitative descriptive literature. The data findings are in the form of narrative quotations based on the formulation of the problem. The data collection technique uses content analysis sourced from the object of the novel research. The results of the ecological culture research in the novel include: (i) the natural environment, (ii) the cultural environment, and (iii) the social environment. Through these ecological culture findings, it is shown that the lives of the people in Kon Village are friendly with nature. Social activities are also directly related to nature.Keywords:narrative; ecological culture; literary ecoanthropology